Is it wrong to try to pick up girls in a dungeon? 4 - Omori, Fujino; Kunieda (Yen Press, 2016)
"With the help of his supporter, Lilliluka, and with his keen desire to become stronger burning within him, Bell Cranell reaches level ten of the Dungeon. The monsters they discover in that foggy place are terrible hulking brutes--orcs! Bell plunges into battle when something different attacks him from behind--but what? Magic, betrayal, and the forging of new bonds, all in the fourth volume of this familia myth--lived by the boy and chronicled by the goddess!"--Page [4] of cover.